Application of pseudo-fluid approximation to evaluation of flow velocity through gravel beds - Cheng, Nian-Sheng (2014)
Flows seeping through a gravel bed are usually non-Darcian and closely related to non-linear drag. Such flows may be significantly affected by particle shape and bed configuration. In this study, a pseudo-fluid model is developed to calculate average flow velocity through gravel beds. The proposed approach is able to take into account particle shape effect using the drag coefficient associated with an isolated sediment grain and also bed configuration effect in terms of apparent viscosity. The model was then calibrated with ten series of laboratory data, which were collected using vertical columns packed with spherical and natural gravels. Finally, the model was successfully applied to estimate total flow discharges for laboratory-scale open channel flows over a gravel bed.